Financial Analysis to Measure PT Hutama Karya Financial Performance Period 2020-2022 - Afrindah Saktia; Nabila Sawitri (INCOME: Innovation of Economics and Management, 2023)
Through the use of financial ratios, this study seeks to ensure the financial performance of PT Hutama Karya. This study examines numerical data, including financial statements from PT Hutama Karya income statement 2020 to 2022 and statement of financial position, using quantitative descriptive analysis methodology. According to research findings, the poor performance of PT Hutama Karya as indicated by the liquidity ratio (current ratio, quick ratio) is caused by the company's reduced ability to meet the approaching maturity. PT Hutama Karya financial performance is characterized by unhealthy solvency ratios (debt to equity, debt to asset ratio) because its total debt continues to increase every year. When considering profitability statistics (ROA, ROE, ROI, and operating profit margin), PT Hutama Karya low financial performance can be attributed to the inadequate performance of the company's management in overseeing its operations.